Chemical Synthesis of Sialyl N‐Glycans and Analysis of Their Recognition by Neuraminidase. Issue 46 (7th October 2021) - Shirakawa, Asuka; Manabe, Yoshiyuki; Marchetti, Roberta; Yano, Kumpei; Masui, Seiji; Silipo, Alba; Molinaro, Antonio; Fukase, Koichi
Abstract: The chemical synthesis of a fully sialylated tetraantennary N ‐glycan has been achieved for the first time by using the diacetyl strategy, in which NHAc is protected as NAc2 to improve reactivity by preventing intermolecular hydrogen bonds. Another key was the glycosylation to the branched mannose in an ether solvent, which promoted the desired glycosylation by stabilizing the oxocarbenium ion intermediate. Furthermore, high α‐selectivity of these glycosylation reactions was realized by utilizing remote participation. Two asymmetrically deuterium labeled sialyl N ‐glycans were also synthesized by the same strategy. The synthesized N ‐glycans were used to probe the molecular basis of H1N1 neuraminidase recognition. The asymmetrically deuterated N ‐glycans revealed a difference in the recognition of sialic acid on each branch. Meanwhile, the tetraantennary N ‐glycan was used to evaluate the effects of multivalency and steric hinderance by forming branching structures. Abstract : Two biantennary N ‐glycans with asymmetrically deuterium labeled sialic acid groups were synthesized through a convergent approach that also enabled the first chemical synthesis of a fully sialylated tetraantennary N ‐glycan (see scheme). The synthesized N ‐glycans were used to probe the molecular basis of H1N1 neuraminidase recognition.